Cdc42 functions as a regulatory node for tumour‐derived microvesicle biogenesis - Wang, Jing; Zhuang, Xiangjin; Greene, Kai Su; Si, Ha; Antonyak, Marc A.; Druso, Joseph E.; Wilson, Kristin F.; Cerione, Richard A.; Feng, Qiyu; Wang, Hongyang (Journal of extracellular vesicles, 2021)
Tumour‐derived microvesicles (MVs) serve as critical mediators of cell‐to‐cell communication in the tumour microenvironment. So far, the underlying mechanisms of MV biogenesis, especially how key tumorigenesis signals such as abnormal EGF signalling regulates MV release, remain unclear. Here, we set out to establish reliable readouts for MV biogenesis and then explore the molecular mechanisms that regulate MV generation. We found that Rho family small G protein Cdc42 is a convergent node of multiple regulatory signals that occur in MV biogenesis. The binding of activated GTP‐bound Cdc42 and its downstream effector, Ras GTPase‐activating‐like protein 1 (IQGAP1), is required for MV shedding. Activated Cdc42 maintains sustained EGF signalling by inhibiting the internalization of cell surface receptors, including EGFR and the VEGF oligomer, VEGF90K, and then facilitates MV release. Subsequently, we further demonstrated that blocking these signalling pathways using the corresponding mutants effectively reduced MV shedding and significantly inhibited MV‐promoted in vivo tumour angiogenesis. These findings reveal a complex regulation of MV shedding by tumour cells, shedding light on the regulatory mechanism of MV biogenesis, and potentially contributing to strategies that target MVs in cancer therapy.